THE CORRELATION BETWEEN EDUCATION, ECONOMIC STATUS, OCCUPATION, PARENTING, AND MOTOR DEVELOPMENT IN TODDLERS 12-60 MONTH - Melani Melani; Artika Putri (ALINEA: Health Science & Medical International Journal, 2024)
Background: The stage of toddlerhood is a critical phase characterized by significant physical and cognitive progress. Delayed growth and development refers to a situation when a child fails to achieve the expected stage of growth and development at the proper age. Purpose: The objective of this study is to establish the correlation between education, economic status, employment, and parenting, as well as the motor development of toddlers aged 12-60 months. Method: The research methodology employed in this study is qualitative research utilizing a Cross-Sectional research design. The population in this study consisted of 280 mothers with toddlers. A sample size of 99 respondents was selected using the purposive selection technique. The study was conducted from December 2022 to February 2023 at Posyandu Melati in Batam City. Result: The findings indicated that 53 respondents (53.5%) possessed a moderate level of education, 60 respondents (60.6%) had an economic status as determined by MSE, 63 respondents (63.6%) were unemployed, 58 respondents (58.6%) exhibited terrible parenting, and 60 respondents (60.6%) displayed problematic motor development. Conclusion: The economic status, occupation, and parenting habits of individuals considerably impact the motor development of toddlers. There exists a correlation, however not statistically significant, between the level of education and the motor development of toddlers.